Diagnosa Dini Penyakit Mata Menerapkan Metode Case Based Reasoning (CBR) - Prasetyo, Dwi Yuli; Rianto, Bayu; Rais, Muhammad Sandi; Suwanti, Nurita (STMIK Budi Darma, 2021)
The eye is a sense organ found in humans. The eye has the ability to adjust the amount of light that enters, focus attention on objects near and far and produce a continuous image and is conveyed to the brain. Distractions that cause damage to the eyes, can occur due to eye fatigue, lack of sleep, exposure to dust, too long in front of the computer and so on. This study aims to analyze and design an expert system for early diagnosis of diseases of the eye that includes disease information, both symptoms and solutions, and plays a role in replacing and mimicking the reasoning process of an expert in solving specification problems. The method used for reasoning is case base reasoning (CBR) and the results of the study are an expert system for early diagnosis of computerized eye diseases that can be used to provide useful information in diagnosing disease